(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
While the exceptio veritatis (defence of the truth) clause enjoys a long tradition in Spanish Criminal Law as a defence against prosecution for criminal libel (calumny), there is an on going debate among the scholars over its legal nature. This paper studiesthe role of the exceptio veritatis clause: some general considerations are followed by a conceptual examination of the criminal offence of libel and a concise review of its inclusion in successive Spanish Criminal Codes enacted from 1822 on. Finally, the paper describes the main positions on the legal nature of this clause.